If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+3x-6x=6-3x-3
We move all terms to the left:
3+3x-6x-(6-3x-3)=0
We add all the numbers together, and all the variables
3x-6x-(-3x+3)+3=0
We add all the numbers together, and all the variables
-3x-(-3x+3)+3=0
We get rid of parentheses
-3x+3x-3+3=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 2/5x+11=4/5x-17 | | 2x+x-0.4=113.4 | | 2x-1=3/4x=9 | | 3/4k*9=6 | | 2x+4-0.4=113.4 | | -7=p/15-1 | | 23x+3=17x+7 | | 7x-3x=-6(x+10)+-15-15x | | 14+-3=4x | | -7(3x-5)=-70 | | 9x^2+90x=0 | | 8x-5=-7 | | 12=8-3(n-1) | | 1+5n=-7+4n-5n | | -2=f+13 | | 4-2x-x+7=x+3+4 | | z/3+6=7 | | 12x-30=8x+26 | | -x+6+2x=4x-4 | | x-2(-4)=6 | | 47-k=34 | | G(x)=2x^2+x-6 | | -6/n=3 | | -3(8+3x)=-87 | | 2x-0.4=113.4 | | 5(7n-1)+4=31+3n | | -(9/4)v+4/5=7/8 | | 4d-11=15-19d | | 4x+6x+15=55 | | (t^2+4t+4)^2=0 | | 9x-15-2x=3(-20+30x) | | -8=12-x/4 |